2009
DOI: 10.1016/j.biomaterials.2009.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive injectable hyaluronic acid hydrogel for adipose tissue engineering

Abstract: A series of thermosensitive copolymer hydrogels, aminated hyaluronic acid-g-poly(Nisopropylacrylamide) (AHA-g-PNIPAAm), were synthesized by coupling carboxylic end-capped PNIPAAm (PNIPAAm-COOH) to AHA through amide bond linkages. AHA was prepared by grafting adipic dihydrazide to the HA backbone and PNIPAAm-COOH copolymer was synthesized via a facile thermo-radical polymerization technique by polymerization of NIPAAm using 4,4′-azobis(4-cyanovaleric acid) as an initiator, respectively. The structure of AHA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
240
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(247 citation statements)
references
References 40 publications
0
240
4
Order By: Relevance
“…20 As shown in the spectrum, the peaks at 1.1 ppm ( Figure 3C) and 3.9 ppm ( Figure 3D) are assigned to −CH 3 and −NH-groups, respectively. The DS values of PNIPAAm controlled by the feed mole ratio of PNIPAAm-COOH are shown in Table 1.…”
Section: Results and Discussion Synthesis And Characterization Of Ha-mentioning
confidence: 99%
See 1 more Smart Citation
“…20 As shown in the spectrum, the peaks at 1.1 ppm ( Figure 3C) and 3.9 ppm ( Figure 3D) are assigned to −CH 3 and −NH-groups, respectively. The DS values of PNIPAAm controlled by the feed mole ratio of PNIPAAm-COOH are shown in Table 1.…”
Section: Results and Discussion Synthesis And Characterization Of Ha-mentioning
confidence: 99%
“…A prior study has demonstrated the usefulness of hyaluronic acid-g-poly(N-isopropylacrylamide) (HAg-PNIPAAm) microgels as an injectable hydrogel for adipose tissue engineering. 20 However, as far as we know, very little work has been done regarding the use of HA-g-PNIPAAm microgels for ophthalmic application.…”
Section: Introductionmentioning
confidence: 99%
“…Its high, tissue-like water content and porous structure allows the influx of low molecular weight solutes and nutrients crucial to cellular viability, as well as the transport of cellular waste out of the hydrogel [3]. As biomaterials, the use of injectable hydrogels also allows the administration of the material through minimally invasive techniques, to fill any area with a good physical integration into the defect, to incorporate cells or various therapeutic agents (e.g., growth factors) with a facile and homogenous distribution within any defect [4][5][6][7]. Therefore, hydrogels have been identified to be suitable as bone and cartilage repair materials because they can be carriers for growth and morphogenetic factors to exert host cell chemotaxis, proliferation, differentiation and new tissue formation at the site of injury or defect [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they can be processed under relatively mild conditions and delivered in a minimally invasive manner. Chitosan also inhibits the growth of many types of fungi, yeasts, and bacteria [35][36][37][38]. All these features make it an attractive option for several applications, such as in food and nutrition, medicine, microbiology, immunology, agriculture, and veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%